THE USE OF DRILLING TECHNIQUES INTEGRATED WITH TECHNOLOGY TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SD NEGERI 9 KARANGASEM - Putu Ratih, I Dewa Ayu; Dewi, Kadek Sintya; Mahendrayana, Gede (Universitas Suryakancana, 2025)
This research is a Classroom Action Research. The subjects in this study were fourth grade students of SD Negeri 9 Karangasem, totaling 20 students. The purpose of the research was to improve vocabulary mastery through drilling technique integrated with technology and to identify students' opinions about the implementation. Data collection techniques used vocabulary test and interview. The research procedure includes stages: planning, action, observation and reflection. Based on the results of the study, it can be concluded that through drilling techniques integrated with technology can improve students' vocabulary mastery. This is evident from the students' scores on the vocabulary test from the pre-test with a score of 61.25 to 78.25 in cycle I and 85 in cycle II with a record of all students exceeding the KKTP. In addition, all students stated that the use of drilling technique integrated with technology was very interesting, motivating and improved vocabulary mastery. Thus, it can be concluded that through drilling technique integrated with technology can improve students' vocabulary mastery in class IV of SD Negeri 9 Karangasem.